Acellular Wharton's Jelly, Potentials in T-Cell Subtypes Differentiation, Activation and Proliferation - Mehdi Talebi; Hojjatollah Nozad Charoudeh; Ali Akbar Movassaghpour Akbari; Behzad Baradaran; Tohid Kazemi (Tabriz University of Medical Sciences, 2020)
Purpose: Because of different potentials of T-cell subtypes in T-cell based cellular immunotherapy approaches such as CAR-T cell therapies; Regarding the high cost of the serum-free specific culture media, having distinct control on T-cell subset activation, expansion and differentiation seem crucial in T-cell expansion step of cell preparation methods. By the way, there was no clear data about the effect of acellular Wharton's Jelly (AWJ) on T-cells expansion, activation or differentiation status. So, we have launched to study the effect of AWJ on T-cell's immunobiological properties. Methods: CD3+ T-cells were isolated from healthy bone marrow allogeneic donors, sorted by FACS method and cultured on either routine phyto-hemagglutinin complemented and different concentrations of AWJ, lag phase and doubling time of the cells calculated from cell growth curve. After 3, 7 and 14-days T-cell subtypes cell markers and cell activity related genes expression rate have been evaluated by flow cytometry and real-time polymerase chain reaction (PCR) methods respectively. Results: AWJ in a 1:1 ratio compared with contemporary lymphocyte culture media showed significant activating and proliferative capacities. The introduced condition has not affected the frequency of CD4+ subpopulation of T-cells, but significantly increased even CD8+ cells and immune-activator genes in T-cells. The regulatory and memory subsets of T-cells in this study have not affected significantly. Conclusion: the study results revealed that AWJ can be utilized as a supportive substance to increase the memory properties of the T-cells, gives control to design a selective medium for expanding and differentiating memory T-cells, relatively.